Institutionalizing Climate Change Adaptation and Mitigation Through Education in a Small Island Context: A Case Study of South Tabukan, Sangihe Islands - Heliani, Leni Sophia; Hadianti, Atrida; Nayati, Widya; Dewanto, Bondan Galih; Putri, Citra Kumala; Aqso, Muhammad Raihan; Pratama, Rizki Febri; Listyana, Deswita; Sanjaya, Darmawan Dwi (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
The Sangihe Islands Regency, one of Indonesia’s small and outermost island regions, has been increasingly affected by the impacts of climate change. Extreme weather events and high waves have contributed to a decline in both the quantity and quality of fish catches and agricultural yields, which are the primary sources of livelihood for many residents. However, the community’s understanding of climate change, including its causes, impacts, mitigation strategies, and adaptation measures, remains limited. In response, a comprehensiveand community capacity-building program was initiated, focusing on education and institutionalization related to climate change mitigation and adaptation. The initiative was structured around four action clusters: medical, agricultural, science and technology, and socio-humanities. These efforts resulted in the development of environmentally friendly systems for waste disposal, agriculture, capture fisheries, and water resource management. The initiative is expected to strengthen the foundational capacities of residents in South Tabukan, Sangihe Islands Regency, enabling them to independently and sustainably mitigate and adapt to the impacts of climate change.